Seismic Characterization of Hypogenic Karst Systems Associated with Deep Hydrothermal Fluids in the Middle-Lower Ordovician Yingshan Formation of the Shunnan Area, Tarim Basin, NW China - Hongtao Zhu; Xiu Zhu; Honghan Chen (Geofluids)
Two fundamental forms of hypogenic karst systems (lateral stratiform hypogenic and cross-formational fault-vein hypogenic karst system) are distinguished mainly by differential effects of preexisting faults. In seismic cross sections, hypogenic karst systems are expressed as complex string-beads-like seismic reflections associated with faults. In this study, a new seismic characterization workflow was developed including seismic amplitude thresholding, fault interpretation, pickup, and merge display to enhance the description of the spatial distribution and coupling of hypogenic karst system and faults. The results suggest that the lateral stratiform hypogenic karst systems are predominantly developed at the top of the secondary faults, presenting an overall of “layered distribution and finger-like interaction” features. The cross-formational fault-vein hypogenic karst systems are developed around faults and characterized by dendritic distribution. Furthermore, we infer that the development pattern of hypogenic karst systems has been produced by the interplay of the faults, preexisting epigenic karst systems, and lateral carrier-beds, which together combine the complex hydrothermal migration pathways of fluids with the characteristics of vertical and horizontal combined pathways. In addition, some possible controlling factors (e.g., sequence stratigraphic boundaries, paleogeomorphology, and sedimentary facies) that can influence the development of these hypogenic karst systems have been discussed in detail.